PENGEMBANGAN MEDIA LEMBAR BALIK TENTANG DETEKSI DINI PENYAKIT DIABETES MELITUS DI POSBINDU RW 03 DESA MALAKASARI - Haliza Zahro, Azkiya; Iryanti, Iryanti (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: The high number of DM cases in Indonesia based on SIMPTM data (2022) is due to the low coverage of early detection which has only reached 25.5%. In line with the survey results of the Indonesian Ministry of Health (2021) 2 out of 3 people with DM do not know they have DM, this is influenced by knowledge factors. The development of flip sheet media can be used as an alternative to DM early detection education media that has not existed before. This is based on research conducted by Niu Flora which states that the flip sheet media is effective for use as educational media because it can increase target knowledge. Research Purposes: To produce a flip sheet media about early DM disease education in Posbindu RW 03 Desa Malakasari that can be used in early detection of DM disease. Methodology: RnD with 4D module approach. Conducted at Posbindu. Qualitative research samples used 5 cadres with 'purposive sampling' technique, interview guideline instruments, descriptive analysis of media feasibility questionnaire instruments, quantitative descriptive analysis using percentage and 'mean' formulas. Results: : Shows the results of the feasibility test value of material experts 95%, language experts 100%, media experts 94% and target groups 89%. Conclusion: The flip sheet media on early detection of diabetes mellitus is very feasible to use.